Illuminating perceptions about communication in environmental consultancy organizations - Ryberg, Hampus (2020)
Environmental consultant organizations deal with solving environmental problems. In this process of solving environmental problems communication is an important and integral part. How consultant organizations perceive communication has an effect on how they develop strategies for communication. By conducting seven semi-structured interviews, this study investigates how consultants working for environmental consultancy organizations perceive communication in their work with clients and what meta-theories about communication that informs the development of communication strategies. The study aims at highlighting aspects of communication that are of importance for the work the environmental consultants engage in, aspects of their work which might not be of focus in a day to day setting. By using the data from the interviews, themes that represent how the consultants talk about communication are identified. These themes are then analysed and discussed from the perspective of two metatheories about communication, transmission of messages and symbolic interactionism. The study shows that depending on the objective with the communication, the consultants perceive communication differently. It is common for the consultants to perceive communication as corresponding to the transmission model of communication. But approaching communication with the perspective of symbolic interactionism highlights important aspects of communication that otherwise might not be revealed. Analysing different ways of approaching communication allows for a discussion about how to approach communication in environmental consultant organizations.